Protection And Utilization Of Protected Forests In Ambon City Environmental Law Prespective - Richard Marsilio Waas; Welly Angela Riry (Balobe Law Journal, 2022)
Introduction: Protected Forest is a forest area that has a variety of vital ecosystem services for the welfare and resilience of society and the economy in the future. Excessive use of forests by humans without regard to the ecological balance can cause havoc for humans themselves, and require economic and social costs that are far greater than the economic results that have been obtained. Often people who live and make a living around the forest are accused of being one of the causes of forest destruction, but also the people who live around the forest are also expected to be the main actors for efforts to protect the forest itself.Purposes of the Research: to understand the protection and utilization of protected forests in Ambon City and to determine the form of policy by the Ambon City Government in protecting and utilizing protected forests in Ambon City from the perspective of Environmental Law.Methods of the Research: The research method uses the Social Legal Research method with a legal, conceptual, and case approach.Results / Findings / Novelty of the Research: The protection and utilization of protected forests in Ambon city has not explicitly been regulated in the form of regional regulations on protected forests. The use of protected forests is still carried out by indigenous peoples and forest rights holders. This shows that the policy regarding the protection and utilization of protected forest areas has not been maximized in the city of Ambon, which will greatly impact all aspects of human life and other habitats.